2011
DOI: 10.1089/pho.2010.2858
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Induced Healing of Diabetic or Venous Foot Ulcers: A Placebo-Controlled Double-Blind Study

Abstract: In this small scale placebo-controlled double-blind study, broadband (400-800  nm) visible light was an effective modality for the treatment of leg or foot ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 21 publications
0
40
0
4
Order By: Relevance
“…At the end of the follow up, all of the wounds in 9 of the treatment group patients were closed (90%) whereas in the placebo group, only 2 of 6 patients (33%) had closed wounds, judged by Wagner's classification for foot ulcer and wide/length measurement. There were no adverse therapy effects [20]. …”
Section: Resultsmentioning
confidence: 99%
“…At the end of the follow up, all of the wounds in 9 of the treatment group patients were closed (90%) whereas in the placebo group, only 2 of 6 patients (33%) had closed wounds, judged by Wagner's classification for foot ulcer and wide/length measurement. There were no adverse therapy effects [20]. …”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27] Specifically, a PBM approach has shown promising efficacy in VLU treatment. [28][29][30] The photo-converter wound gel is presented in two jars, which have to be mixed together just prior to application. Typically, upon evaluation, any excess fibrin or necrotic tissue was debrided.…”
mentioning
confidence: 99%
“…Landau Z et al, demonstrated effects of hyperbaric oxygen along with laser. 13 Treatment time was 20mins for 2-3weeks. 81% of refractory diabetic foot ulcers were healed by this method.…”
Section: Discussionmentioning
confidence: 99%